Landasan Epistemologi dalam Pengembangan Kurikulum PAI pada Mata Pelajaran Akidah Madrasah Ibtidaiyah - Unil Ilma, Miska (Epistemic: Jurnal Ilmiah Pendidikan, 2023)
The development of the Islamic Religious Education (PAI) curriculum is essential in addressing contemporary needs and challenges, both from within the education system and external influences, such as new understandings that might alter religious perspectives in Indonesia. This research specifically examines the Aqidah Akhlak (Faith and Ethics) component within the PAI curriculum at Madrasah Ibtidaiyah (Islamic elementary schools), focusing on its epistemological foundations. The study aims to explore how these foundations can effectively shape students' attitudes and characters as religious individuals and societal members. Utilizing a descriptive qualitative methodology with a library study approach, data were collected from various literature sources, including the Minister of Religious Affairs Decree No. 183 of 2019 on the PAI Curriculum. The research design involved analyzing this data to understand the theoretical framework and practical implications. Key findings suggest that a robust understanding of the epistemological foundations in Aqidah Akhlak teaching is crucial for achieving the educational goals set by the curriculum. This understanding helps in selecting appropriate teaching materials, methodologies, and ensuring that the curriculum remains responsive to contemporary challenges. The study's implications underscore the importance of epistemological foundations in enhancing the effectiveness of Aqidah Akhlak education at Madrasah Ibtidaiyah.